Political Particularism around the World - Jessica Seddon Wallack; Alejandro Gaviria; Ugo Panizza; Ernesto H. Stein (Inter-American Development Bank, Research Department, 2002)
This paper presents a new dataset on electoral systems and outlines its potential uses in further research exploring the connections between electoral systems and economic outcomes. The dataset provides indicators of the degree to which individual politicians can further their careers by appealing to narrow geographic constituencies on the one hand, or party constituencies on the other.
Keywords: 330; Wahlsystem; Karriereplanung; Politiker; Wirtschaftspolitik; Welt